ABC of prescribing exercise as medicine: a narrative review of the experiences of general practitioners and patients. Issue 2 (2nd June 2021) - O'Regan, Andrew; Pollock, Michael; D'Sa, Saskia; Niranjan, Vikram
Abstract : Background: Exercise prescribing can help patients to overcome physical inactivity, but its use in general practice is limited. The purpose of this narrative review was to investigate contemporaneous experiences of general practitioners and patients with exercise prescribing. Method: PubMed, Scopus, Science Direct and Cochrane reviews were reviewed using the terms 'exercise prescription', 'exercise prescribing', 'family practice', 'general practice', 'adults' and 'physical activity prescribing'. Results: After screening by title, abstract and full paper, 23 studies were selected for inclusion. Qualitative, quantitative and mixed-methods studies revealed key experiences of general practitioners and patients. Barriers identified included: physician characteristics, patients' physical and psychosocial factors, systems and cultural failures, as well as ambiguity around exercise prescribing. We present a synthesis of the key strategies to overcome these using an ABC approach: A: assessment of physical activity: involves asking about physical activity, barriers and risks to undertaking an exercise prescription; B: brief intervention: advice, written prescription detailing frequency, intensity, timing and type of exercise; and C: continued support: providing ongoing monitoring, accountability and progression of the prescription. Multiple supports were identified: user-friendly resources, workshops for doctors, guidelines for specific illnesses and multimorbidity, electronic devices, health system support and collaboration with other healthcare and exercise professionals. Discussion: This review has identified levers for facilitating exercise prescribing and adherence to it. The findings have been presented in an ABC format as a guide and support for general practitioners to prescribe exercise.